2013
DOI: 10.1371/journal.pone.0083936
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Analysis in Familial Non-Lynch Syndrome Colorectal Cancer Families from Sweden

Abstract: Family history is a major risk factor for colorectal cancer and many families segregate the disease as a seemingly monogenic trait. A minority of familial colorectal cancer could be explained by known monogenic genes and genetic loci. Familial polyposis and Lynch syndrome are two syndromes where the predisposing genes are known but numerous families have been tested without finding the predisposing gene. We performed a genome wide linkage analysis in 121 colorectal families with an increased risk of colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Previous linkage studies have identified several candidate regions on different chromosomes, but the only one in the present study, which resembles any of the published regions, is 9q [ 6 , 7 , 14 , 39 41 ]. The region identified in the present study (the variants in the genes OR13C8, EPB41L4B, SEC16A and NOTCH1 ), is just proximal to that region on 9q.…”
Section: Discussionmentioning
confidence: 54%
“…Previous linkage studies have identified several candidate regions on different chromosomes, but the only one in the present study, which resembles any of the published regions, is 9q [ 6 , 7 , 14 , 39 41 ]. The region identified in the present study (the variants in the genes OR13C8, EPB41L4B, SEC16A and NOTCH1 ), is just proximal to that region on 9q.…”
Section: Discussionmentioning
confidence: 54%
“…46 Current understanding suggests that the risk alleles identified are insufficient to independently account for FCCTX, but a combination of moderate and low-risk alleles could contribute to the familial aggregation. 4,[39][40][41][42]47 Genomic and epigenetic profiles of FCCTX-associated colorectal cancer Deranged DNA methylation is inversely associated with the MSI and the CpG island methylation phenotypes (CIMP) and has been demonstrated in 30-40% of colorectal cancers. [48][49][50][51][52] Hypomethylation in long interspersed nucleotide element-1 (LINE-1) has been linked to familial CRC, including FCCTX, and is thought to interfere with chromosomal segregation and thereby enhance chromosomal instability (CIN).…”
mentioning
confidence: 99%
“…In the linkage analysis, the genetic analyses were performed as described, 16 although this time 45 families with at least one case of PrC or GC were used and subdivided into three different analysis groups: all 45 families were analyzed in one CRC, PrC, and GC syndrome group, 32 families in the CRC and PrC syndrome groups, and 22 families in the CRC and GC syndrome groups (see Table 1). The analysis was executed twice for all three groups.…”
Section: Genotyping In the Linkage Analysismentioning
confidence: 99%